Species composition and age ratio of rock ptarmigan (Lagopus muta) and willow grouse (Lagopus lagopus) shot or snared in the county of Västerbotten : possible implementations for grouse winter management - Brandt, Alisa (SLU/Dept. of Wildlife, Fish and Environmental Studies, 2016)
Hunting has a long tradition in Sweden and is also nowadays well established in society, provides considerable income through hunting tourism and functions as an important wildlife management and conservation tool. The most popular game species in the Swedish mountains are willow grouse (Lagopus lagopus) and rock ptarmigan (Lagopus muta). Those two species are closely related and managed together as one unit in Sweden but differ distinct in population size, with rock ptarmigan showing a smaller population size than willow grouse. Their similar appearance makes it difficult to take preventive actions like setting different quotas for the two bird species before the hunt. This shows the importance of bag statistics and the accuracy of the species identification by hunters and trappers. Identification is assumed to be most difficult during the last months of the hunting season from January to March. During these last months both species have a white winter plumage and show only little difference in species specific characteristics but also no direct visible difference between ages. Therefore a second management issue is the eventuality of a non deliberate age selective hunting mortality and the eventual divergent impact of trapping and shooting on this. To investigate these issues shot or snared rock ptarmigan and willow grouse were examined through the last month of the hunting season. Hunters and trappers in the area of Saxnäs, Grönfjäll and Tärnaby were visited and more wing and foot samples could be aquired through hunters sending them by mail. To be able to study the consistency to the hunters reports, different species identification factors were tested for their reliability. Additionally the species and age composition, meaning the juvenile (< 1 year) to adult (> 1year) ratio, in the bag of hunters and trappers was analyzed. Bodyweight and wing length turned out to be a rather unreliable identification method while the appearance of a black stripe across the eyes, claw colour and the location, in ...